Parents' Religious Considerations When Choosing A School: Marketization of Faith-Based Primary Schools in Indonesia. - Rifal Yoga Pratama; Catur Sugiarto (Management Analysis Journal, 2023)
This study aims to explain the phenomenon of marketization of faith-based elementary schools in Indonesia, the increase in new students in Islamic schools is often linked to the religious awareness of parents. So an investigation was carried out related to the religiosity of parents with their consideration in choosing an elementary school. This study used a qualitative method by involving parents who had different opinions in the consideration of choosing a school. The investigation into parental religiosity was obtained through interviews with 20 parents. Supporting informants: 1 religious teacher and 1 member of the ministry of religion. Broadly speaking, religious parents emphasize a more conscious attitude towards the importance of religious knowledge for their child, with a postulate: the investment in the afterlife. In addition, other considerations of parents place more emphasis on moral education than academic achievement. This study takes a new perspective on the marketization of faith-based primary schools integrated with parental religiosity. By exploring their considerations in choosing the ideal school according to their self-image